The Economic Impact of IMF-Supported Programs in Low-Income Countries - Bal Gunduz, Yasemin; Ebeke, Christian; Hacibedel, Burcu; Kaltani, Linda (Washington, D.C. : International Monetary Fund, 2013)
This paper aims to assess the economic impact of the IMF's support through its facilities for low-income countries. It relies on two complementary econometric analyses: the first investigates the longer-term impact of IMF engagement-primarily through successive medium-term programs under the Extended Credit Facility and its predecessors (and more recently the Policy Support Instrument)-on economic growth and a range of other indicators and socioeconomic outcomes; the second focuses on the role of IMF shock-related financing-through augmentations of Extended Credit Facility arrangements and short-term and emergency financing instruments-on short-term macroeconomic performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet